Realization and Application of Customer Attrition Early Warning Model in Security Company - Liu Bin; Qiu Huayong; Shen Yizhen (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
In this paper, we propose the customer attrition early warning model based on data warehouse and data mining technologies, which is achieved and applied in our security company. The modeling variables can be selected by means of the combination with decision tree and the gradual regression in Logistic regression. Then customer attrition early warning model can be constructed based on Logistic regression. The results show that the model can strongly promote the customer attrition capturing rate, push on the building of the company customer marketing management and customer service management organization, and economize the marketing cost. The company profits promotion and trade competitive power can be promised. DOI: http://dx.doi.org/10.11591/telkomnika.v10i5.1270